2016
DOI: 10.1021/acs.jafc.5b06150
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Penicillin G Metabolites under Various Environmental Conditions Using UHPLC-MS/MS

Abstract: In this work, we investigate the stability of penicillin G in various conditions including acidic, alkaline, natural acidic matrices and after treatment of citrus trees that are infected with citrus greening disease. The identification, confirmation, and quantitation of penicillin G and its various metabolites were evaluated using two UHPLC-MS/MS systems with variable capabilities (i.e., Thermo Q Exactive Orbitrap and Sciex 6500 QTrap). Our data show that under acidic and alkaline conditions, penicillin G at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…Using the Orbitrap and triple-quadrupole based UHPLC-MS/MS platforms, we analyzed a citrus fruit sample taken from a HLB infected tree that was treated with penicillin G; the presence of the metabolites penillic acid, isopenillic acid, penilloic acid, and penicilloic acid were confirmed. Penicillin G was not found in the citrus sample, however this was anticipated, as environmental conditions on the growing field, such as heat, UV radiation, and acidic conditions of the fruit would contribute heavily to degradation after treatment [65,66].…”
Section: Penicillin G and Its Metabolitesmentioning
confidence: 87%
See 2 more Smart Citations
“…Using the Orbitrap and triple-quadrupole based UHPLC-MS/MS platforms, we analyzed a citrus fruit sample taken from a HLB infected tree that was treated with penicillin G; the presence of the metabolites penillic acid, isopenillic acid, penilloic acid, and penicilloic acid were confirmed. Penicillin G was not found in the citrus sample, however this was anticipated, as environmental conditions on the growing field, such as heat, UV radiation, and acidic conditions of the fruit would contribute heavily to degradation after treatment [65,66].…”
Section: Penicillin G and Its Metabolitesmentioning
confidence: 87%
“…This analytical technique is recognized for its exceptional specificity and selectivity, and its advantages were well suited to characterizing the degradation of penicillin G. Under acidic conditions, penicillin G is shown to have a rate of degradation of 0.29 h -1 corresponding to a half-life of 2.4 hrs at pH 2 when the concentration of penicillin G was 100 ng/mL. Penicillin G was not detectable after approximately 10-15 hours [65]. Our UHPLC-MS/MS analysis of penicillin G's degradation at pH 2 confirmed that penillic acid is the predominant species formed in acidic conditions, resulting in approximately 60% of the total metabolites ( Figure 3A).…”
Section: Penicillin G and Its Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a rapid and effective method for the simultaneous effective separation and rapid determination of anthraquinones, including emodin and physcion, in Liupao tea via UHPLC‐MS was developed and verified using HPLC. UHPLC‐MS is a rapid and effective method used in detecting various fungal metabolites (Natalia et al ; Aldeek et al ) and analysing agricultural residue in tea (Zhang et al ). The retention times of emodin and physcion in our method were 4·878 and 4·241 min, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, penicillin G can be degraded in alkaline or acidic pH and in the presence of β-lactamase into different metabolites, including benzyl penilloic acid or benzylpenillic acid. A list of known chemical structures, including penicillin G and its metabolites (27, 28), were targeted with the following parameters: 0.1 minutes retention time window, 5 % CCS tolerance, 5 ppm m/z tolerance on parent adducts (H+ and Na+) and 10 mDa m/z tolerance on predicted fragments. Retention times and CCS values were previously measured from penicillin G degradation experiments at pH 2 and pH 10 in order to perform subsequent accurate structures screening.…”
Section: Methodsmentioning
confidence: 99%